Model Of Variation Of Thing Practice In Handball Game For Students Of Madrasah Aliyah Pku Tidung Island - Bisri Mustofa; Mustafa Masyhur; Slamet Sukriadi (Advances In Social Humanities Research, 2023)
Thesis I explain about variation models exercise throwing handball for madrasah aliyah students , this research method uses Research and Development (R&D) research using ADDIE theory . In this research , 15 training models were created , which have been through validation tests from three expert field the categorized as from easy _ to the difficult , the results of This research aims as reference material teachers in providing more models and methods used in the training process To use improve training results and abilities in basic handball passing techniques . And as a reference students who will later create them thesis with similar material.